Paradoxy of modernism - Scholes, Robert, 1929-2016 (Yale University Press, 2006)
Robert Scholes intervenes in ongoing discussions about modernism in the arts during the crucial half-century from 1895 to 1945 he contends that the binary oppositions which defined modernism are misleading. He argues that such oppositions are instances of 'paradoxy', an apparent clarity that covers real confusion.